Strategi Guru Pendidikan Agama Kristen Dalam Membentuk Karakter Peserta Didik Di Era Digital - Ebenezer Gulo; Denisman Laia; Sandra Rosiana Tapilaha (Publisher STPKat, 2024)
The author concludes that a Cristian religious education teacher has an important role in shaping the character of students in the digital era. Integrating Cristian values in the currculum, discussion and reflfection can help build a moral foundation. The example set by teacher and colla boration w ith parents is also important to provide concrete examples. Supervision, guidance and literacy edukation in a literacy context also help form strong character amidst the vast and varied flow of digital information. Teaching from Cristian religious education teacher can provide a strong foundation to shape students’ character based on moral and spiritual values in the mids of the ever-growing dogital era so that students become individuals with character and responsibility and ethics in using technological tools in the digital era.